Role of Subjective Norm in Investment Decision Making of Casual Investors - Sharma, Meenakshee; Gupta, Sumeet (Indian Journal of Finance, 2011)
Casual investors are those who have less knowledge about basic finance and more or less do not make big calculations for making their investment decisions. Financial theories, such as Markowitz portfolio theory attempts to pin down investment decision-making in terms of risk and return. However, a number of studies as well as theories from consumer behavior suggest that risk and return are just two facets of investment decision and should be seen as a part of a bigger framework. In this study, the authors integrate theories from finance and psychology (theory of planned behavior) to develop a model of investment decision making for casual investors. In addition to the belief based evaluation (risk Vs return), theory of planned behavior suggests that subjective norms (social influence) and behavioral control also influence one's decision. Applying the theory of planned behavior, the authors found that apart from risk-return evaluation, subjective norm (financial advisor's influence) has a significant bearing on casual investors' investment decision.